Implementasi Program Adiwiyata Nasional Berbasis Kearifan Lokal di SMP Negeri 1 Ngadirojo - Maryatmo, Pudi Sri; Juhana, Juhana; Winarni, Retno (Universitas Mathla'ul Anwar Banten, 2023)
Implementation of the National Adiwiyata Program Based on Local Wisdom to Improve the Character of Students at SMP Negeri 1 Ngadirojo, Wonogiri Regency is a description of the process of implementing various school efforts in collaboration with other parties involved in helping to shape and develop the character of students who care about the environment, care about the environment, are disciplined, creative, And Responsibility. The purpose of this study was to describe the planning, implementation, and results of the Adiwiyata program at SMP Negeri 1 Ngadirojo. This type of qualitative descriptive research. Data collection was carried out during August to November 2021 using interview, observation, and documentation techniques. The data were analyzed qualitatively with the following stages: data collection, data reduction, data display and conclusion drawing. The results showed that: (1) Adiwiyata program planning began by forming an adiwiyata team, at the initial stage the adiwiyata team compiled an environmental study which was then prepared an action plan to form an 5 (five) characters that must be possessed by students, namely: environmental care character, social care character, discipline character, creative character, and responsibility character that is integrated in all subjects. (2) The implementation of the adiwiyata program begins with classroom learning and extracurricular activities, (3) the adiwiyata program at SMP Negeri 1 Ngadirojo results in changes in the behavior of school residents, especially students and changes in the physical environment of the school. Changes in student behavior are marked by the formation of 5 (five) student characters, namely environmental care, social care, discipline, creativity, and responsibility